Caracterização da vegetação, da composição física e química do solo e da serapilheira em área de transição Amazônia-Cerrado - Mützenberg, Dalila Morgana de Souza (2020)
Among the different forest formations that the Cerrado biome transitions, aboute 24% of the area occurs between two of the largest Brazilian biomes, the Cerrado and the Amazon Forest, representing one of the transition zones. The Cerrado-Amazon transition area is one of the regions most affected by the advance of agriculture, transforming it into forests with characteristics of unstable and hyperdynamic forests. Thus, the objective of this study was to characterize the local vegetation, the physical and chemical composition of the soil, the litter production and the decomposition rate in an Amazon-Cerrado transition area, in Campo Novo do Parecis. The study area is located around the Small Hydroelectric Power Plant (PCH) Baruíto. The experiment was conducted in a transition forest fragment from January 2012 to December 2013, divided between 5 transects (A, B, C, D and E) with 21 points marked at a spacing of 5 in 5 meters, totaling 100 meters . In order to identify the species, a phytophysiognomic survey was carried out, characterizing species of greater occurrence, being species from the Cerrado, the Amazon or the Cerrado-Amazon. The most abundant families were Melastomataceae, Myrtaceae and Myristicaceae. The species Virola sebifera showed higher ICR and IIR. With a diameter distribution of less than 10 cm, it is characterized as a young forest fragment. The cycling of nutrients is mainly influenced by the content of available organic matter that influences the distribution of other nutrients. The retention of some chemical elements is limited due to the sandy characteristic of the soil. The accumulated and produced litter was higher during the dry season. The total decomposition rate was higher during the dry-rainy transition while the total decomposition rate was higher in the rainy-dry transition with k = 0.39 coefficient. Corroborating with our hypothesis, it is observed that when comparing transition forest with biome like the Cerrado, transition forests present greater litter in the drought and higher decomposition rate. However, with a slower total decomposition coefficient k in relation to a biome such as the Amazon, the study site is not yet in dynamic equilibrium.